(untitled) (Qualitative Research Journal for Social Studies, 2026)
Political discourse often appears clear and authoritative, yet it is shaped by language, ideology, and power. Deconstruction, associated with Jacques Derrida, challenges the stability of meaning by revealing contradictions, binary oppositions, and hidden assumptions within texts. This approach is particularly useful for analyzing political speeches that construct specific narratives rather than presenting neutral realities. In the context of the U.S.–Iran conflict, the speeches of Donald Trump reflect themes of power, national security, and global tension. Using a qualitative deconstructive approach, selected lines from these speeches are analyzed to identify hidden assumptions, contradictions, and binary oppositions. The analysis shows that meanings in the speeches are not fixed but unstable and relational. Concepts such as progress, power, and stability depend on their opposites, including limitation, vulnerability, and crisis. The coexistence of opposing ideas—such as peace and aggression—further reveals internal tensions within the discourse. Overall, the study demonstrates that political language constructs reality rather than simply describing it and meaning remains open to multiple interpretations.